Accuracy Assessment of Classical Isothermal Experiment in Drug Storage Period Studies - Jiafu Feng; Zhigui Zhang; Dixiao Yang (Journal of Pharmacy and Nutrition Sciences, 2014)
The purpose of this research was to assessment the effect of change of dissolved oxygen concentration on accuracy of classical isothermal experiment in ascorbic acid solution storage period studies. The experiments were performed at temperatures 35 ˚C, 40 ˚C, 45 ˚C and 50 ˚C, the apparent rate constant (kA) and the adjusted apparent rate constant (kA,A) were determined, respectively. By plotting lnkA and lnkA,A against 1/T resulted two lines, respectively. Then the apparent rate constant at 25 ˚C, kA,25˚C =5.168×10-4(mol×L-1×h-1) and the adjusted apparent rate constant at 25 ˚C, kA,A,25˚C=5.157×10-4(mol×L-1×h-1), was extrapolated, respectively. Both the calculated storage period of the experimented ascorbic acid solution were all 55h by kA,25˚C and kA,A,25˚C， respectively. The results suggested that the change of dissolved oxygen concentration has no effect on the accuracy of classical isothermal experiment in ascorbic acid solution storage period studies.